2012
DOI: 10.1186/1471-2164-13-663
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing and de novo transcriptome analysis of Costus pictus D. Don, a non-model plant with potent anti-diabetic properties

Abstract: BackgroundPhyto-remedies for diabetic control are popular among patients with Type II Diabetes mellitus (DM), in addition to other diabetic control measures. A number of plant species are known to possess diabetic control properties. Costus pictus D. Don is popularly known as “Insulin Plant” in Southern India whose leaves have been reported to increase insulin pools in blood plasma. Next Generation Sequencing is employed as a powerful tool for identifying molecular signatures in the transcriptome related to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…In this respect, traditional medicines possess great potential [3,4]. More and more plant products and their preparations have been used for therapeutic purposes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, traditional medicines possess great potential [3,4]. More and more plant products and their preparations have been used for therapeutic purposes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…De novo assembly of transcriptome has been widely used to identify the biosynthetic and regulatory genes in non-model organisms, such as Thapsia laciniata, 18) Costus pictus, 19) and Curcuma longa. 20) These transcriptome data have accelerated our understanding of the complexity of gene transcription patterns, gene structure variances, and gene regulation networks.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing gave direct evidence for their presence. Similarly, in plant Costus pictus transcripts, proofs of some of these compounds were identified (Annadurai et al 2012). In addition, transcriptome analysis of this insulin plant (Hegde et al 2014) revealed presence of transcripts involved in bixin and geraniol biosynthesis.…”
Section: Revealing Unidentified and Novel Bioactive Principlesmentioning
confidence: 98%